PEMAHAMAN KONSEP AKUNTANSI BAGI SISWA SMA TARSISIUS 1 JAKARTA - Lukman, Hendro; Lie, Michelle; Eugenia, Ashley (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Accounting is a social science that is different from other social sciences. Accounting science has more to do with calculations and laws or rules like exact sciences. Thus, learning accounting will not be more effective if followed by extensive and comprehensive training. Studying accounting in schools is generally not equipped with accounting practice laboratories that comprehensively discuss training such as SMA Tarsisius 1 Jakarta. SMA Tarsisius 1 Jakarta provides special accounting lessons for Social Sciences (IPS) students when they are in class XII. Based on these considerations, the Accounting Undergraduate Study Program, Faculty of Economics and Business, Tarumanagara University organizes an Accounting Practice Laboratory as an extracurricular activity at SMA Tarsisius 1 Jakarta specifically for class XII IPS students, and for students who wish to study accounting. In this activity, it is the first meeting which is the initial discussion given to students. Discussion on understanding the concept of accounting which includes accounting definitions, accounting equations, accounting cycles, forms of trade and service business reports, and compiling lists of estimates. This material is the basis for discussing other continuous topics. The learning outcomes at this stage were considered very successful which were assessed through the answers to exercises and quizzes given to students, as well as the evaluation at the end of the meeting. The implications of this activity are that students have accounting skills, the school as a partner has added value, and for Tarumanagara University as a marketing medium. Akuntansi adalah ilmu sosial yang berbeda dengan ilmu sosial lainnya. Ilmu akuntansi lebih banyak berhubungan dengan hitungan dan hukum atau aturan seperti ilmu eksakta. Dengan demikian, belajar akuntansi tidak akan lebih efektif jika diikuti dengan latihan yang banyak dan komprehensif. Belajar akuntansi di sekolah umumnya tidak dilengkapi dengan laboratorium praktik akuntansi yang membahas latihan secara komprehensif seperti SMA Tarsisius 1 Jakarta. SMA Tarsisius 1 Jakarta memberikan pelajaran akuntansi khusus untuk siswa Ilmu Pengetahuan Sosial (IPS) ketika mereka duduk di kelas XII. Berdasarkan pertimbangan ini, program studi sarjana Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tarumanagara menyelenggarakan Laboratorium Praktik Akuntansi sebagai kegiatan ekstrakurikuler di SMA Tarsisius 1 Jakarta khusus untuk siswa kelas XII IPS, dan bagi siswa yang ingin belajar akuntansi. Dalam kegiatan ini, adalah pertemuan pertama yang merupakan pembahasan awal yang diberikan ke siswa. Pembahasan mengenai pemahaman konsep akuntansi yang meliputi pengertian akuntansi, persamaan akuntansi, siklus akuntansi, bentuk laporan usaha dagang dan jasa, dan menyusun daftar perkiraan. Materi ini adalah landasan untuk membahas topik lainnya yang berkesinambungan. Hasil pembelajaran tahap ini dinilai sangat berhasil yang dinilai melalui jawaban latihan dan kuis yang diberikan kepada siswa, serta evaluasi pada akhir pertemuan. Implikasi dari kegiatan ini diharapkan siswa memiliki keterampilan akuntansi, sekolah sebagai mitra memiliki nilai tambah, serta bagi Universitas Tarumanagara sebagai media pemasaran.